1984
DOI: 10.1126/science.224.4656.1443
|View full text |Cite
|
Sign up to set email alerts
|

Acetolactate Synthase Is the Site of Action of Two Sulfonylurea Herbicides in Higher Plants

Abstract: Biochemical and genetic studies of a tobacco mutant resistant to the herbicides chlorsulfuron and sulfometuron methyl have demonstrated that these sulfonylurea herbicides inhibit acetolactate synthase, the first enzyme specific to the branched chain amino acid biosynthetic pathway. Resistance of this mutant is accomplished by production of a form of the enzyme that is insensitive to inhibition by the two herbicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
220
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 416 publications
(229 citation statements)
references
References 9 publications
7
220
0
1
Order By: Relevance
“…Detoxification of the herbicide in tolerant crops is by hydroxylation of the phenyl ring, followed by conjugation with a plant carbohydrate (Sweetser et al, 1982). Chaleff and Mauvais (1984) and Ray (1Y84) analyzed the resistance at the molecular level and have shown that growth inhibit10n in tobacco is caused by CS binding to and inactivating the acetolactate synthas~ enzyme (ALS). The same mechanism exists for bacteria (LaRossa and Schloss, 1984), yeast (Falco and Dumas, 1985) and other higher plants such as…”
Section: (King and Evans 1983)mentioning
confidence: 99%
See 4 more Smart Citations
“…Detoxification of the herbicide in tolerant crops is by hydroxylation of the phenyl ring, followed by conjugation with a plant carbohydrate (Sweetser et al, 1982). Chaleff and Mauvais (1984) and Ray (1Y84) analyzed the resistance at the molecular level and have shown that growth inhibit10n in tobacco is caused by CS binding to and inactivating the acetolactate synthas~ enzyme (ALS). The same mechanism exists for bacteria (LaRossa and Schloss, 1984), yeast (Falco and Dumas, 1985) and other higher plants such as…”
Section: (King and Evans 1983)mentioning
confidence: 99%
“…Blair (1988) contends that metabolism is likely the basis of tolerance, as ALS extracted frnm tolerant plants, wheat and oats, is as sensitive to CS inhibilion as ALS from sensi ti ve plants, such as peas and soybeans. However, Chaleff and Mauvais (1984), using tobacco suspension cultures, isolated CS resistant lines and found that the phenotype was inherited as a single dominant or semidominant mutation in the ALS gene, and that thi~ single nuclear gene mutation was responsible for resistance exhibited at the whole plant level.…”
Section: (King and Evans 1983)mentioning
confidence: 99%
See 3 more Smart Citations